2017
DOI: 10.1063/1.4998395
|View full text |Cite
|
Sign up to set email alerts
|

Competition between the inter-valley scattering and the intra-valley scattering on magnetoconductivity induced by screened Coulomb disorder in Weyl semimetals

Abstract: Recent experiments on Weyl semimetals reveal that charged impurities may play an important role. We use a screened Coulomb disorder to model the charged impurities, and study the magnetotransport in a two-node Weyl semimetal. It is found that when the external magnetic field is applied parallel to the electric field, the calculated longitudinal magnetoconductivity shows positive in the magnetic field, which is just the negative longitudinal magnetoresistivity (LMR) observed in experiments. When the two fields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The recent experiments triggered a renewed interest in the problem leading to the appearance of a number of theoretical studies reproducing and extending Abrikosov's earlier results. [27][28][29][30][31][32][33][34] Notably, the more realistic situation with a pair of nodes was accounted for in Refs. 27, 28, 30, and 33, while disorder was assumed to be of (uncorrelated) Gaussian white noise type in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The recent experiments triggered a renewed interest in the problem leading to the appearance of a number of theoretical studies reproducing and extending Abrikosov's earlier results. [27][28][29][30][31][32][33][34] Notably, the more realistic situation with a pair of nodes was accounted for in Refs. 27, 28, 30, and 33, while disorder was assumed to be of (uncorrelated) Gaussian white noise type in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…And the high order bubble diagrams have the nontrivial effect on the longitudinal conductivity. To our knowledge, the influence of inter-valley scattering on the magnetoresistance of WSM begins to draw attention [46]. But the contribution of hight order terms must be treated carefully.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Considering the relatively high carrier density of Te flakes arising from the large amounts of Te vacancies, the screened Coulomb potential may effectively affect the magnetotransport behaviors by introducing both the intra-valley scattering and intervalley scattering. [43] As the temperature decreases, the intervalley scattering takes a more important role in the transport behavior, as evidenced by the emergence of weak localization as well as the violation of Kohler's rule (see Note 3 and Fig. S6 in the supplementary material), leading to a transition from parabolic to linear field dependence of the longitudinal MC.…”
mentioning
confidence: 99%
“…Note that in the theory developed by Son and Spivak, [40] there is an important assumption that the intra-valley scattering determines the transport performance while the intervalley scattering is negligible. [42] Ji et al [43,44] further explored the effects of both intra-valley and inter-valley scattering induced by the screened Coulomb potential, and revealed that the linear longitudinal MC is actually closely relevant to the enhanced contribution of the inter-valley scattering. Considering the relatively high carrier density of Te flakes arising from the large amounts of Te vacancies, the screened Coulomb potential may effectively affect the magnetotransport behaviors by introducing both the intra-valley scattering and intervalley scattering.…”
mentioning
confidence: 99%